If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -55 = 12x Reorder the terms: -55 + 7x = 12x Solving -55 + 7x = 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -55 + 7x + -12x = 12x + -12x Combine like terms: 7x + -12x = -5x -55 + -5x = 12x + -12x Combine like terms: 12x + -12x = 0 -55 + -5x = 0 Add '55' to each side of the equation. -55 + 55 + -5x = 0 + 55 Combine like terms: -55 + 55 = 0 0 + -5x = 0 + 55 -5x = 0 + 55 Combine like terms: 0 + 55 = 55 -5x = 55 Divide each side by '-5'. x = -11 Simplifying x = -11
| 21+4(2n-11)=1 | | -3y-15=2(17-5y) | | 3x-10=9x | | 10y=9(y+13) | | 2X-15=83 | | 3(4-2.25x)=25 | | 4x+15-3x=-8-11 | | -8-12=4x+18-3x | | 13x-8=14x | | 8y+4=7(y-1) | | y=(x^2)(sinx)(tanx) | | 5-(4-9)= | | -8x+4+9x=-13+3 | | 6z^2-37z-553=0 | | 3x+5=175 | | y+4.4=-7.7-8.2 | | 10-3x=-5k | | 4x^2-44=1835 | | -2-4=-8+x | | x-.4=4.4 | | -7+17t= | | -23+11=m-8 | | 6x+10=12x-8 | | 5(x-2)-3(x-2)=2x+4 | | 5t-12t= | | x+1overx=6 | | 14x(x-y)+(x-y)=0 | | 6x-2(-6x+7)=130 | | 2(x^2-476)=0 | | 42=-7x | | 510=-10(-8x+5) | | ln(x)=ln(8)-2ln(x) |